P162 The impact of day-case multidisciplinary assessment on asthma control and quality of life scores of patients referred to the manchester severe asthma service. (12th November 2019) - Holmes, LJ; Elsey, L; Sommerton, C; Tavernier, GA; Allen, D
Abstract : Introduction: 250, 000 individuals are affected by severe asthma, which can cause a huge physical and psychological burden. Severe asthma requires a comprehensive and systematic assessment, to confirm diagnosis, distinguish the correct phenotype, identify co-existing conditions and tailor therapy. Historically our initial assessment of the referred patient was dictated by a traditional medical model. We have redeveloped our processes to facilitate a daycase multi-disciplinary (MDT) systematic assessment for all patients referred to our service. Methods: A retrospective review of patient records from baseline assessment and their 12-week follow-up was performed, to assess their initial outcomes after attending the MDT assessment. Results: In the first 6 months 100 patients were referred 94% had a pre-existing diagnosis of asthma and 63% were female. Day-case assessment identified a primary diagnosis of atopic asthma (25%), eosinophilic asthma (34%), neutrophilic asthma (6%), occupational asthma (1%), and mixed phenotype or differential diagnosis (24%/10%). By second visit we had confirmed co-diagnosis of Tracheo-bronchomalacia n=20(20.4%), inducible laryngeal obstruction n=13(13.1%) and breathing pattern disorder n=20 (20.6%). Comparison of Asthma Control (ACQ) at baseline to 12 weeks review shows an overall improvement of 0.75 (m=0.75, SD 1.5 t (78)4.43, p<0.001) and a 0.76 (z=-2.7, p=0.005) improvement in Asthma quality of life (AQLQ). Poor inhaler technique was demonstrated by 48 (62%), fair technique by 17(22%) and good technique by 12(15%). Only 8.1% had an asthma action plan on referral. Through delivery of educational intervention at baseline, the ACQ at 12 weeks has shown the highest improvement in the group with the poorest technique dropping by 0.96(CI 0.45–1.4). The fair technique group dropped by 0.5 (CI 0.08–0.92) and good technique dropped by 0.4 (CI 0.11–0.93). Similarly, the non-adherent group (collection of <80% prescription refills) at baseline n=18 (25.3%) showed an improvement in their ACQ of 1.1 (C I 0.28–1.9), when compared to the adherent groups n=53(74%) ACQ of 0.67(CI 0.28–1.07). Conclusion: Our results indicate that poor control may in part be due to poor adherence and inaccurate diagnosis. Through adopting an MDT systematic assessment, we can consider differential diagnosis and demonstrate an improvement in ACQ and AQLQ with a significant positive patient feedback.